Overview of Judgments of the Constitutional Court of Georgia - Constitutional Court of Georgia (Journal of Constitutional Law)
The Journal of Constitutional Law continues to provide readers with an overview of the recent case law of the Constitutional Court of Georgia. For the current issue, four landmark judgments of the Constitutional Court have been selected for publication. The editorial board of the journal hopes that this overview of the Court’s practice will enhance the level of legal debates concerning the Court’s activities.